PERBEDAAN PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN COOPERATIVE LEARNING TIPE JIGSAW TERHADAP PRESTASI BELAJAR SEJARAH DITINJAU DARI KEMANDIRIAN BELAJAR (STUDI EKSPERIMEN PADA SISWA KELAS XI DI SMA NEGERI KABUPATEN KENDAL) - Novikasari, Wardani; Wasino, W.; Suryani, Nunuk (Sebelas Maret University (UNS), 2018)
This study aims to analyze: (1) influence of difference of use of model learning Problem Based Learning and Cooperative learning model of the Learning type of achievement against learning the history of the Jigsaw students; (2) the influence of the difference between students who have high and Self-reliance and independence of students with low learning achievements against the history of students; (3) use of model learning influence interactions with Independence of learning achievement against learning history students. This research uses a quantitative approach to the type of research experiments, with 2 x 2 factorial design. The population in this research is the whole grade XI Senior High School of Kendal. Sampling technique used is a dwarf in the Multi Stage Random Cluster Sampling. The instrument used is now learning and achievement test independence of learning. Test the hypothesis used is Anava two lanes. Before the hypothesis testing is done, test the normality of equality test, and the test of its homogeneity. The results of this research indicate that: (1) there may be differences influence the use of model learning Problem Based Learning and Cooperative Learning learning achievements against Jigsaw type history students, viewed from a F calculate > F table, or 11, 144 > 3, 14; (2) there may be differences between the influence of the students who have high Independence and self-reliance, and students who have low achievement students study history, seen from F calculate > F tables, or 14, 748 > 3, 14; (3) there are no interactions influence the use of models of learning with the learning independence towards the achievements of the students study history, seen from F to calculate F < table, or 0, 026 < 3, 14.Â